Adaptive management: A practical guide to mitigating uncertainty and advancing evidence-based programming - Byom, K.; Ingram, M.; Oakley, A.; Serpe, L. (PACT, 2020)
Pact’s Adaptive Management Guide provides practical guidance to development practitioners globally on the mindsets, behaviors, resources, and processes that underpin an effective adaptive management system. It presents an approach to managing adaptively that is rooted in complexity analysis and program theory. It draws on Pact’s global experiences and work on topics as diverse as health, livelihoods, markets, governance, capacity development, women and youth, and more. This document begins with an introduction to adaptive management, then walks through successive steps to determine how much adaptation a project requires and how to design an appropriate system. The second half of this guidebook contains a toolkit of examples and templates that projects can tailor to their needs.

The Strategy Testing Workbook: Politically-Smart Adaptive Programming in Complex Environments - Nixon, Nicola; O'Donnell, Carolyn; Rajalingam, Gobie; Tweedie, Pauline; Sullivan, Elizabeth (The Asia Foundation, 2024)
The guide begins with a section on what we at TAF have learned about practicing Strategy Testing, highlighting things that we didn’t know when we started out. Some of these lessons may seem obvious, but others may strike you as less so. In any case, we believe that, when taken together, they provide a useful reminder of some of the pitfalls that arise in efforts to practice Adaptive Management. Moreover, they help to remind us that there are multiple layers to doing Strategy Testing effectively as a system instead of reducing it to its component parts and applying them mechanistically. Thus these lessons are useful to read now and to revisit later. The guide then comprises three more sections: • Part 1, the Design Stage, involves constructing the system and making sure everyone is on board; • Part 2, the Inception Phase (start-up phase), helps the implementing team to make the leap from the ideal initially set out in the design stage to the grounding, support, and frameworks that the team will need to implement Strategy Testing in a meaningful and impactful way. We’ve found that the gap between design and implementation is very often the cause of an ineffective ‘all talk and no walk’ approach to Adaptive Management. And finally; • Part 3 covers Program Implementation – the practices, knowledge, and culture needed for the feedback loop that underpins Strategy Testing. The guide can be used for individual or group learning, or it can be used directly to inform Reflection Sessions (see Section 3) through the questions we raise or the activities herein.

A Systems Framework for International Development: The Data-Layered Causal Loop Diagram - Blair, Courtney; Gralla, Erica; Wetmore, Finley; Goentzel, Jarrod; Peters, Megan (Production and Operations Management, 2021)
Meeting the United Nations Sustainable Development Goals (SDGs) will require adapting or redirecting a variety of very complex global and local human systems. It is essential that development scholars and practitioners have tools to understand the dynamics of these systems and the key drivers of their behavior, such as barriers to progress and leverage points for driving sustainable change. System dynamics tools are well suited to address this challenge, but they must first be adapted for the data-poor and fragmented environment of development work. Our key contribution is to extend the causal loop diagram (CLD) with a data layer that describes the status of and change in each variable based on available data. By testing dynamic hypotheses against the system's actual behavior, it enables analysis of a system's dynamics and behavioral drivers without simulation. The data-layered CLD was developed through a 4-year engagement with USAID/Uganda. Its contributions are illustrated through an application to agricultural financing in Uganda. Our analysis identified a lack of demand for agricultural loans as a major barrier to broadening agricultural financing, partially refuting an existing hypothesis that access to credit was the main constraint. Our work extends system dynamics theory to meet the challenges of this practice environment, enabling analysis of the complex dynamics that are crucial to achieving the SDGs.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/poms.13492

Track to Change | Home - Clear Horizon (Clear Horizon, 2025)
Track to Change homepage

Participation for Humanitarian Innovation - Toolkit - Smith, Amy; Thompson, Martha; Saida Benhayoune; Crespo Cardona, Omar (Elrha, 2023)
A resource designed to help organisations, teams and individuals manage innovation journeys responsibly and successfully. We have partnered with MIT D-Lab to develop a new resource to drive greater diversity and inclusion within project design and implementation. The Participation for Humanitarian Innovation (PfHI) toolkit sets out a robust approach to setting expectations for and monitoring the degree of participation within research and innovation projects for, with, and by people affected by crisis. The PfHI toolkit is composed of five tools: Opportunity Adviser: Identify and prioritise the desired benefits of participation while weighing the potential barriers. Participation Matrix: Agree on the precise degree of participation to target at a given project stage. Resource Navigator: Select tools and processes to address the needs of stakeholders, the project objectives and context. Quality Guidance: Ensure engagements are delivered to the highest standard. Assessment Matrix: Collectively evaluate the degree of participation achieved during an activity or project phase, learn and adapt. By applying these tools before, during and after a research and/or innovation project, implementors can ensure that stakeholders/end-users are included and participating at the highest possible degree. We encourage users of the PfHI toolkit to consider how else to integrate the tools into existing practices. For instance, the Evaluation Matrix could be used to supplement existing MEAL activities to: Establish baselines to measure changes in participation over time. Track the degree of participation/engagement of stakeholders. Regularly assess the degree of participation. Seek feedback from participants about the degree of their participation. Monitor the progress of activities related to stakeholder engagement. Our Participation for Humanitarian Innovation toolkit represents our ongoing commitment to responsible research and innovation across our portfolio of grants and for the humanitarian sector more broadly. We hope you will consider downloading and using the toolkit on your next project.